IL-33 Aggravates DSS-Induced Acute Colitis in Mouse Colon Lamina Propria by Enhancing Th2 Cell Responses - Junfeng Zhu; Fangli Yang; Lixuan Sang; Jingbo Zhai; Xiaoqing Zhang; Dan Yue; Shengjun Li; Yan Li; Changlong Lu; Xun Sun (Mediators of Inflammation)
Interleukin- (IL-) 33, a member of the IL-1 cytokine family, is an important modulator of the immune system associated with several immune-mediated diseases. IL-33 was expressed in high level on epithelial cells of intestinal tract. It suggested that IL-33 plays a potential role in inflammatory bowel diseases (IBD). We investigated the role of interleukin- (IL-) 33 in dextran sulphate sodium- (DSS-) induced acute colitis in mice using recombinant mouse IL-33 protein (rIL-33). We found that DSS-induced acute colitis was aggravated by rIL-33 treatment. rIL-33-treated DSS mice showed markedly reduced levels of interferon- (IFN-)γ and IL-17A in their colon lamina propria lymphocytes (LPL), but the levels of Th2 cytokines, such as IL-5 and IL-13, in these cells were significantly increased, compared to DSS mice treated with PBS. Our results suggested that IL-33 stimulated CD4+T cells and caused the cell to adopt a Th2-type response but at the same time suppressed Th17 and Th1 cell responses. Therefore, IL-33 may be involved in pathogenesis of DSS-induced acute colitis by promoting Th2 cell response in intestinal mucosa of mice. Modulation of IL-33/ST2 signaling by monoclonal antibody (mAb) could be a novel biological therapy in DSS-induced acute colitis.